Identification of polyphenolic compounds in the flesh of Argan (Morocco) fruits - Khallouki, Farid; Ricarte, Írvila; Ulrich, Cornelia; Owen, Robert (Food chemistry, 2015)
High performance liquid chromatography coupled with negative electrospray ionization (HPLC-ESI) along with fragmentation patterns generated by nano-electrospray ionization (nano-ESI-MS-MS) and NMR techniques were utilized for the identification of phenolic compounds in Argan fruits. A total of 15.4 g/kg was determined represented by catechins (39%), flavonoids (28%), procyanidins (26%), free phenolic acids (6%) and phenolic acid glycosides (1%). Twenty-one phenolic compounds were identified for the first time in Argan fruits namely III. epicatechin-(4β → 8)-catechin dimer (procyanidin B1), IV. p-coumaric acid glycoside, VI. epicatechin-(4β → 8)-epicatechin dimer (procyanidin B2), VIII. caffeic acid glycoside, XIX. epicatechin-(4β → 8)-epicatechin-(4β → 8)-epicatechin trimer (procyanidin C1), X. p-hydroxybenzaldehyde XI. ferulic acid glycoside, XII. vanillic acid, XIII. sinapic acid glycoside, XVI. p-coumaric acid, XVII. ferulic acid, XVIII. sinapic acid, XIX. rutin pentoside, XX. quercetin glycopentoside, XXI. 4,4′-dihydroxy-3,3′-imino-di-benzoic acid, XXV. quercetin-3-O-rhamnogalactoside, XXVII. quercetin glycohydroxybenzoate, XXVIII. quercetin glycocaffeate, XXIX. quercetin glycosinapate, XXX. quercetin glycoferulate and XXXI. quercetin glycocoumarate.